Development of a Control System for a Domestic Grid-Connected Wind Turbine - Adamson, Michael Angus; Muhammad-Sukki, Firdaus; Aziz, Nur Fadilah Ab; Abu-Bakar, Siti Hawa; Sellami, Nazmi; Iyi, Draco; Ramirez-Iniguez, Roberto; Bani, Nurul Aini; Mas’ud, Abdullahi Abubakar; Munir, Abu Bakar; Yasin, Siti Hajar Mohd (American Scientific Publishers, 2019)
In the United Kingdom (UK), homeowners who install grid connected renewable energy sources receive a threefold benefit. They can use the electricity generated by the source, they enjoy reduced household bills and they can also receive Feed-in Tariff payments from the UK government. Tariffs are paid for generating electricity and for exporting electricity back to the grid. Savings can be maximized by correctly managing the ratio of number of units consumed by the homeowner to the number of units exported to the grid. In order to achieve a low percentage export situation, it was postulated that a control system would be needed. This paper proposes a control system for a small wind turbine based on an Arduino Uno microcontroller. The system was designed and built in order to evaluate its effectiveness. Results showed that the control system was effective in ensuring a low percentage export. When immediate domestic demand was met, surplus electricity was diverted to a storage circuit. Only as a last resort, when domestic and storage demand was met, was electricity exported. A cost analysis of the system showed that having a control system incorporated as part of the wind turbine installation could lead to savings of more than 12,000 over the life of the product. Copyright © 2019 American Scientific Publishers All rights reserved.